Successful development and implementation of a practical proactive resistance management plan for Bt cotton in Australia. Issue 10 (29th July 2021) - Knight, Kristen M; Head, Graham P; Rogers, D John
Abstract: This article describes the design and > 20 years of effective implementation of a proactive resistance‐management plan for transgenic Bacillus thuringiensis (Bt) cotton that targets Helicoverpa armigera (Hübner) and Helicoverpa punctigera (Wallengren) in Australia, considering pest biology and ecology, insights from resistance‐evolution modelling, and the importance of the human component to effective implementation. This is placed in the context of processes associated with adaptive resource management. Bt cotton has provided Australian cotton growers with technology to manage Helicoverpa species that previously challenged the industry's viability, while at the same time resulting in no detectable changes in the resistance allele frequency in field populations of either Helicoverpa species in eastern Australia. This is the most long‐lived and successful global example of a proactive resistance management plan for an insect pest. Six key learnings important to the successful development and implementation of a proactive transgenic‐crop resistance management plan are: the programme has to have a strong science base; there has to be broad stakeholder support at all levels; there has to be a strong implementation programme; the plan needs to be supported by auditing and enforced remediation of deviations from the mandated resistance management plan; A programme of rigorous and on‐going resistance allele monitoring; an attitude of continuous improvement for all aspects of the resistance management plan. The lessons learnt from the deployment of Bt cotton in Australia are relevant globally and provide important guidelines for the deployment of transgenic crops for insect control wherever they are grown. © 2021 Society of Chemical Industry Abstract : A proactive resistance‐management plan has successfully managed Australian Helicoverpa species on Bacillus thuingiensis (Bt) cotton since 1996 and this success provides guidelines for the global deployment of transgenic crops for pest management.